TEACHING STUDENT'S SPEAKING ABILITY USING TIME TOKEN ARENDS - Mira Nurjanah; Ahmad Hambali; Sri Supiah Cahyati (IKIP Siliwangi, 2018)
Speaking is one of skills that should be mastered by all of students who learn English. However, passive students face some difficulties in speaking. They are less confident, so they difficult to talk in present of the class. Regarding this, the teacher should teach using appropriate strategy to improve students’ speaking ability and to increase their confidence. This research was conducted to find out whether Time Token Arends can improve students’ speaking ability. This research was arranged using Classroom Action Research. The sample taken by using purposive sampling technique. The writers took 32 students of class X IPS 1 in one of a senior high school in Cianjur as the sample of this research. The result showed that Time Token Arends can improve students’speaking ability, especially in encouraging passive students become active students.Aratry. S, Rumiri, A. & Desri, M. S. (2017). The Effect of Please Strategy on the Ability of the first year Students of SMPN 5 Pekan baru in Paragraph writing. FKIP Universitas Riau.Arends, R. (2009). Learning to teach. United States: McGraw Hill.Arikunto, S. (2013). Prosedur Penelitian. Jakarta: PT. Rineka Cipta.Babie, E. (1990). Survey Research Methods (2nd ed.). California: Wadsworth Publishing company, 2nd ed.Brown, H. D. (2001). Principles of Language Learning and Teaching (5 editions). New York: Pearson Education Inc.Hatch, E. M., & Farhady, H. (1982). Research design and statistics for applied linguitics. Rowley, Mass: Newbury House.